Microplastics in terrestrial ecosystem: Exploring the menace to the soil-plant-microbe interactions - Zhai, Yujia; Bai, Junhong; Chang, Pengfei; Liu, Zhe; Wang, Yaqi; Liu, Gang; Cui, Baoshan; Peijnenburg, Willie; Vijver, Martina G. (TrAC, Trends in analytical chemistry (Regular ed.), 2024)
Microplastics (MPs), miniscule plastic particles measuring less than 5 mm in size, have become a concern in terrestrial ecosystems, with primarily agricultural and wetland soils being the soils with highest plastic loadings. The adverse effect of MPs might lead to changes in physicochemical and biological characteristics of soil including soil properties, microbial communities, plants, as well as the potential or affirmed correlations among them. Therefore, understanding the risks and effects of MPs, particularly within the soil-plant-microbe context is challenging and have become a subject of substantial scientific inquiry. This comprehensive review is focused on the effects of MPs on the rhizosphere and plant-microbe symbiotic relationships, with implications for plant growth and ecosystem-level nutrient fluxes. MPs alter soil physicochemical properties, microbial community composition, and enzymatic activities in the rhizosphere, influencing nutrient availability and uptake by plants. These changes in the rhizosphere can disrupt plant-microbe symbiotic interactions, such as mycorrhizal associations and nitrogen-fixing symbioses, ultimately impacting plant growth and the cycling of nutrients within ecosystems. Furthermore, we elaborate on the effects of MPs on the rhizosphere and plant-microbe symbiotic relationships carrying implications for plant growth and ecosystem-level nutrient fluxes. Future research directions and solutions to the microplastics menace acknowledging combined effects of MPs and other contaminants, advanced technologies for MPs identification and quantification, and microbial engineering for MPs remediation. This knowledge of MPs-induced impacts on soil-plant-microbe interactions is essential to generate mitigating actions in soil environmental management and conservation. •MPs affect soil physicochemical properties and plants growth.•MPs in soil reshape microbial community diversity and function.•Microbial degradation of MPs offers promising strategies for mitigation.•MPs disrupt soil-plant-microbe system, cascading impact on terrestrial ecosystems.•Future research is needed for MPs analytical advancement and microbial remediation.